A context-specific approach to L2 motivation in Anglophone settings: a first step towards theory development. Issue 4 (8th August 2018) - Gayton, Angela Mary
ABSTRACT: This study proposes a novel, context-specific, theoretical framework for understanding language learning motivation among secondary pupils in Anglophone settings. It builds on much recent theoretical and empirical work in language learning motivation which has placed increasing emphasis on both the dynamic, fluid nature of motivation, as well as the importance of foregrounding the specific context in which language learning takes place. The framework has also been influenced by teacher interview data, which formed part of a wider multi-strategy investigation into language learning motivation in Scottish secondary schools. Emergent themes include a language teacher's role in mediating the impact of pervasive beliefs about English as a global language, as well as their role in facilitating pupils' development of positive conceptualisations of future selves as successful foreign language users, in both local and global contexts. Recommendations for testing this novel framework with future classroom-based research are made; furthermore, the importance of future work making cross-national comparisons of motivational trajectories in different Anglophone contexts is also acknowledged, given how perceptions of the global spread of English have the potential to negatively impact on language learning in such contexts.